The Influence of Work Environment, Work Discipline and Motivation on Employee Performance - Muhammad Taufik Lesmana; Farhan Anshari Damanik (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The purpose of this study was to determine and analyze the partial and simultaneous effect of environmental variables, work discipline, and work motivation on employee performance at the Regional Tax and Retribution Management Agency of Medan City. This study uses a quantitative approach. The analysis technique used is multiple linear analysis techniques. The results showed a significant effect partially and simultaneously between work environment, work discipline, work motivation on performance